Prophetic Education as a Pillar of Islamic Civilization: An Analysis of Hadith on Taking the Path of Knowledge - Suyudi, Suyudi; Firdaus, Nazilatul Fatihah (Civiliza Publishing, Indonesia., 2025)
The hadith on pursuing the path of knowledge serves as a profound theological and philosophical foundation for the development of Islamic education and the formation of civilization. This study aims to analyze the meaning and relevance of this hadith within the context of prophetic education an educational model that integrates faith, knowledge, and action. The research employs a qualitative library study approach, examining classical and contemporary sources related to Islamic education and prophetic values. The findings reveal that the Hadith positions the pursuit of knowledge as a form of worship with spiritual and social dimensions, functioning as a transformative process toward achieving the ideal human (insan kamil). Prophetic values such as sincerity, perseverance, humility, and moral responsibility serve as the ethical basis for a civilized Islamic education system. Therefore, the hadith on pursuing the path of knowledge is relevant as a paradigm for modern Islamic education that goes beyond knowledge transmission to emphasize character formation and communal well-being. The study recommends further exploration of how prophetic values can be applied in contemporary Islamic educational curricula.